2018
DOI: 10.1177/0284185118770901
|View full text |Cite
|
Sign up to set email alerts
|

Significance of incidental intra-articular and peri-articular FDG avid foci on PET/CT

Abstract: In patients with soft-tissue or osseous sarcomas, isolated FDG avid intra-articular or peri-articular foci without additional metastatic lesions likely represent benign processes. Isolated intra-articular or peri-articular foci with significantly elevated SUV measurements were favored to represent TSGCT in this series.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some case reports state that TSGCT has a high accumulation of FDG, mimicking malignancy and metastasis [ 16 21 ]. The mean SUVmax in patients with TSGCT was higher than the SUVmax in those with benign and non-physiologic pathologies [ 17 ]. West et al reported that TSGCT was related to conditions manifesting features of both reactive inflammatory disorders and clonal neoplastic proliferations involved with abnormal CSF1 expression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some case reports state that TSGCT has a high accumulation of FDG, mimicking malignancy and metastasis [ 16 21 ]. The mean SUVmax in patients with TSGCT was higher than the SUVmax in those with benign and non-physiologic pathologies [ 17 ]. West et al reported that TSGCT was related to conditions manifesting features of both reactive inflammatory disorders and clonal neoplastic proliferations involved with abnormal CSF1 expression [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with diffuse-type TSGCT, joint hemorrhage and repeated local recurrence have been reported to cause joint destruction [ 11 ]. On 18 F-FDG-PET, TSGCT has a high accumulation of fluorodeoxyglucose (FDG) despite it being a benign tumor [ 16 , 17 ]. However, few reports have been published regarding the detailed evaluation of TSGCT using 18 F-FDG-PET/CT.…”
Section: Introductionmentioning
confidence: 99%
“…The most characteristic feature of TGCT/PVNS is its intra-articular location, where it is exceedingly rare for a primary sarcoma or metastasis to originate. If focal intra-articular FDG uptake is associated with an isolated soft tissue mass on FDG PET/CT, MRI should be obtained for further evaluation, as TGCT/PVNS has a distinct heterogeneously low signal intensity on T1 and T2 weighted imaging due to hemosiderin deposits [ 57 ] and may occur more commonly than is generally appreciated [ 58 ] ( Figure 12 ).…”
Section: Jointmentioning
confidence: 99%